KONSEPTUALISASI SUMBER JASA DAN KERUGIAN EKOSISTEM BERDASARKAN KARAKTERISTIK TANAH DI SUB DAS KEMPO, NTB : Conceptualization of Ecosystem Services and Disservices Sources Based on Soil Characteristics in the Kempo Sub-watershed, NTB - Muhammad Anggri Setiawan; Evita Hanie Pangaribowo; Ratih Winastuti (Jurnal Ecosolum, 2021)
One of the natural characteristics of a watershed that ensures the sustainability of ecosystem services is soil. The sustainability of ecosystem services in the Kempo sub-watershed related to soil conditions tends to be in a worrying condition because the sub-watershed is classified as critical. This study aims to describe the relationship between soil characteristics and the sustainability of ecosystem services in the Kempo sub-watershed. Data were obtained from surveys, literature studies, and on-screen digitization of Google Earth images in 2010 and 2019. Modeling of causal loop diagrams using Vensim software. The results show a tendency for ecosystem disservices to occur due to deforestation, which is characterized by the dominance of the negative/balancing behavior type, compared to the positive/reinforcing type. Soil conditions tend to be less supportive of the sustainability of ecosystem services due to high deforestation and intensive monoculture land cultivation. Important changes in the system can be made by addressing deforestation as a significant influence on negative feedback on soil conditions. The CLD model can be used in the development of a framework for assessing ecosystem services and disservices both qualitatively and quantitatively, so further research needs to build dynamic system modeling using Stock Flow Diagrams (SFD).